MAKNA IMPERATIF DALAM TUTURAN PRESIDEN JOKO WIDODO - Aisyah, Siti Nur; Sinaga, Mangatur; ', Charlina (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study discusses the structure of speech that has the imperative meaning and the imperative meaning of President Joko Widodo’s speech. This study aimed to describe the structure of speech that has the imperative meaning and the imperative meaning of president Joko Widodo’s speech. This study practically and theoretically beneficial. It is a qualitative research which utilize descriptive method. This study apply record technique and documentation technique to collect the research data. The data of this research are President Jokowi’s speech on his oration, instruction, opening speech, foreword, interview, dialog, teleconference, conference, and his explanation which has been transcripted by the state secretariat during one hundred of his service periode. The analysis step on this research are data identification, data classification, the analyzing and interpretationof data, and the last is presentation of research proceeds. This study’s object is the languange. The proceeds of this study is a contribution for imperative speech research.Keyword: The Structure of Speech that has Imperative meaning, Imperative Meaning, President Joko Widodo’s Speech.